Effect of Fixed‐Dose Combinations Antituberculosis and Separate Formulations on Clinical Symptoms, Weight Gain, Adverse Effect and Plasma Concentration in Tuberculosis and HIV Coinfection Cases - Sundari, Titi; Mariana, Nina; Permatasari, Debby Intan; Rusli, Adria; Sitompul, Pompini Agustina; Rosamarlina, Rosamarlina; Widiantari, Aninda Dinar; Maemun, Siti; Lisdawati, Vivi (RSUP Dr. Kariadi, 2023)
BACKGROUND: Fixed Dose Combination (FDC) was aimed to simplify TB therapy and facilitate physician and patient compliance. OBJECTIVE: We aimed to evaluate the effect of FDC antituberculosis and separate formulations (SF) on clinical symptoms, weight gain, adverse effect and plasma concentration in TB/HIV cases during the intensive phase. METHOD: Prospective cohort study was conducted in public hospital, Jakarta. We recruited TB-HIV patients in May 2018-May 2019. Patients (over than 18 years old) diagnosed with TB-HIV who consumed either FDC or SF and had not received antiretroviral. A total of 36 subjects were included in this study, 20 subjects in FDC group and 16 subjects in SF group. RESULT: There was not significant different between FDC and SF groups with an improvement of clinical symptoms (P = 0.70) and weight gain (P = 1.00). Gastrointestinal syndrome was 75% in FDC group; 62.5 % in SF group. Mean (±SD) of rifampicin, isoniazid, pyrazinamide plasma concentration after 2 weeks therapy in FDC group were 5.49 mg/L (±3.40 mg/L), 1.35 mg/L (±1.20 mg/L), 19.87 mg/L (±17.00 mg/L), respectively. Mean (±SD) of rifampicin, isoniazid, pyrazinamide plasma concentration in SF group were 6.42 mg/L (±4.80mg/L), 0.87 mg/L (±0.70 mg/L), 5.03 mg/L (±7.60 mg/L), respectively. CONCLUSION: There was not significant different between FDC and SF groups on improvement of clinical symptoms and weight gain in intensive phase of therapy, the highest of adverse effects was gastrointestinal syndrome, and all subjects had normal reference ranges of rifampicin concentrations, and isoniazid and pyrazinamide below the normal range.